(untitled) (World Science, 2018)
The linear differential equation of the internal combustion engine (ICE) itself, by means of which it is possible to investigate the dynamic characteristics (transients) and throttle response of the new generation of gas engines, used as a drive for mobile vehicles, is given. At present, the need has arisen to create a new generation of ICS control systems that would combine the principles of robust and adaptive management and provide a specified quality of management in the conditions of structural or parametric uncertainty of the control facility itself, uncertainty of external conditions and management goal uncertainty. The most important contour in the engine control system is the crankshaft speed regulator. It has a determining effect on the technical, economic and environmental performance of ICE. The resulting differential equation describes the transient processes of the angular velocity variation of the crankshaft of the gas engine of vehicles in a wide range of speed and load modes of operation.